Effects of Mental Imagination on Accuracy of Jump Shot in Basketball - Mohameed, Marwan; Alwan, Wahbi; Swade, Taraq (Journal of Physical Education, 2009)
The aim of this study was to know the effects of Mental Imagination on Jump Shot in Basketball . Twenty youth basketball players took part in this study , age 15,2 ± 1,03 years , height 170,5 ± 6,43 cm and weight 61,9 ± 2.84 kgs . After they did 20 jump shots (pretest) on day 1/12/2004, then this sample divided into tow groups , experimental and control group . The experimental group took ten workouts mental imagination about positive jump shooting after each practice sessions . After that the tow groups made 20 jump shooting on day 27/1/2004 ( post test ) the researcher used proper statistic methods to compare between pre and post tests results The researchers concluded that mental imagination has positive effects on developing jump shots , increase likely shooting success in basketball and strengthens player’s self-confidence by isolating him forum outside environment and interacting him with his inside environment